2021
DOI: 10.48550/arxiv.2110.13917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring the Density Fields around Bright Quasars at $z\sim 6$ with XQR-30 Spectra

Huanqing Chen,
Anna-Christina Eilers,
Sarah E. I. Bosman
et al.

Abstract: Measuring the density of the intergalactic medium using quasar sightlines in the epoch of reionization is challenging due to the saturation of Lyman-α absorption. Near a luminous quasar, however, the enhanced radiation creates a proximity zone observable in the quasar spectra where the Lyman-α absorption is not saturated. In this study, we use 10 high-resolution (R 10, 000) z ∼ 6 quasar spectra from the extended XQR-30 sample to measure the density field in the quasar proximity zones. We find a variety of envi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…If we assume a typical stellar-to-dark-matter mass ratio of ∼ 30 − 50 × 10 −3 appropriate for the high mass end of the halo mass function at z ∼ 6 (Stefanon et al 2021), this would imply a quasar host halo mass of (1 − 2) × 10 12 M . Although the uncertainty of this estimate is large, it is consistent with recent derivations based on the density profile in the proximity zones of z ∼ 6 quasars by Chen et al (2021), who found a typical host halo mass of log 10 (M h /M ) = 12.5 +0.4 −0.7 . (2006).…”
Section: The Quasarsupporting
confidence: 91%
See 1 more Smart Citation
“…If we assume a typical stellar-to-dark-matter mass ratio of ∼ 30 − 50 × 10 −3 appropriate for the high mass end of the halo mass function at z ∼ 6 (Stefanon et al 2021), this would imply a quasar host halo mass of (1 − 2) × 10 12 M . Although the uncertainty of this estimate is large, it is consistent with recent derivations based on the density profile in the proximity zones of z ∼ 6 quasars by Chen et al (2021), who found a typical host halo mass of log 10 (M h /M ) = 12.5 +0.4 −0.7 . (2006).…”
Section: The Quasarsupporting
confidence: 91%
“…One could argue that in principle each quasar at z 6 must have formed in such an overdense environment given their high halo masses (Chen et al 2021). However, the finding of relatively rich environments around quasars such as J0836 and J1030 compared to other quasars must then imply that the conditions required for DCBH formation as suggested by theory may have been particularly well met for the progenitor regions of these sources.…”
Section: Insights Into Seed Formationmentioning
confidence: 99%